Return on Equity, Return on Asset, Net Profit Margin, dan Earning Per Share terhadap Harga Saham Perusahaan Farmasi - Alit Lanang Dandanggula; Erna Sulistyowati (Journal of Management and Bussines (JOMB), 2022)
This study aims to determine the effect of Return on Equity (X1), Return on Assets (X2), Net Profit Margin (X3), Earning per Share (X4) on Pharmaceutical Company Stock Prices for the period 2019-2022 with Company Size as a control variable. This research method is descriptive quantitative. The number of samples taken as many as 14 companies with purposive sampling method. This study uses associative methods and multiple linear regression techniques with SPSS program. The results showed that the regression equation obtained was Y = 5521.001 + 44842.588 X1 + -1153993 X2 + -31580.637 X3 + -4.605 X4 + -154.774 Z. In conclusion, Return on Equity has a positive and significant effect on stock prices, Return on Assets and Earnings. per share has a negative and insignificant effect, while Net Profit Margin has a negative and significant effect on the stock price of pharmaceutical companies. Keywords: Earning per Share, Share Price, Net Profit Margin, Return on Equity, Return on Asset